Analisis Kondisi Kualitas Air pada Budidaya Ikan Kerapu Tikus (Cromileptes altivelis) di Situbondo [Analysis Of Water Quality Conditions On Humpback Grouper Culture (Cromileptes altivelis) In Situbondo] - Abdul Manan; M. Ervany Eshmat N. (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract The humpback grouper (Cromileptes altivelis) is one of the fishery commodities with high economic value in both local and international markets. The price of humpback grouper can reach Rp. 200,000 - Rp. 400,000 / kilogram in the local market. The humpback grouper is potentially to be developed in most coastal areas of Indonesia. The conditions of water quality have a very important role for the success of fish culture of humpback grouper. To that end, monitoring and management of water quality are necessary in fish culture. The purpose of this case study is to determine the water quality conditions on humpback grouper culture in BBAP, Situbondo. The study was conducted on 16 January until 16 February 2012. The study method use descriptive method. From the results of water quality analysis, the water in humpback grouper broodstock ponds (I1 and I2) is no smell, no colour water, temperature 26.1-30 oC, salinity 27-35 ppt, dissolved oxygen 3.3-3.9 ppm, ammonia levels <0.001-0.22 ppm, nitrite levels 0.0075-0.085 ppm, alkalinity 110-120 ppm and pH 7.94-8.18. The water in humpback grouper hatchery ponds (B1 and B2) is no smell, green colour water, temperature 26.7-29.3 oC, salinity 27-34 ppt, dissolved oxygen 2.7-3.7 ppm, ammonia levels 0.0781-0.28 ppm, nitrite levels 0.0225-3.3305 ppm, alkalinity 94-126 ppm, and pH 7.14-7.81.